Taste of control food and the Filipino colonial mentality under American rule - Orquiza, René Alexander D., Jr (Rutgers University Press, 2020)
"Filipino cuisine is a delicious fusion of foreign influences, adopted and transformed into its own unique flavor. But to the Americans who came to colonize the islands in the 1890s, it was considered inferior and lacking in nutrition. Changing the food of the Philippines was part of a war on culture led by Americans as they attempted to shape the islands into a reflection of their home country. Taste of Control tells what happened when American colonizers began to influence what Filipinos ate, how they cooked, and how they perceived their national cuisine. Food historian R. Alexander D. Orquiza, Jr. turns to a variety of rare archival sources to track these changing attitudes, including the letters written by American soldiers, the cosmopolitan menus prepared by Manila restaurants, and the textbooks used in local home economics classes. He also uncovers pockets of resistance to the colonial project, as Filipino cookbooks provided a defense of the nation's traditional cuisine and culture. Through the topic of food, Taste of Control explores how, despite lasting less than fifty years, the American colonial occupation of the Philippines left psychological scars that have not yet completely healed, leading many Filipinos to believe that their traditional cooking practices, crops, and tastes were inferior. We are what we eat, and this book reveals how food culture served as a battleground over Filipino identity"--